2021
DOI: 10.1038/s41390-021-01428-3
|View full text |Cite|
|
Sign up to set email alerts
|

Vital sign metrics of VLBW infants in three NICUs: implications for predictive algorithms

Abstract: Background: Continuous heart rate (HR) and oxygenation (SpO 2 ) metrics can be useful for predicting adverse events in very low birth weight (VLBW) infants. To optimize the utility of these tools, inter-site variability must be taken into account. Methods:For VLBW infants at three NICUs, we analyzed the mean, standard deviation, skewness, kurtosis, and cross-correlation of electrocardiogram HR, pulse oximeter pulse rate, and SpO 2 . The number and durations of bradycardia and desaturation events were also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…External validation will be important because our findings of patterns in vital signs measurements prior to neonatal death might reflect care practices at our hospital. We note, though, the similarity of vital signs measurements at our hospital to those at two others, 45 a finding that is reassuring with regard to the general nature of these results. We found that only 3555 of the 4998 algorithms consistently returned non-null results, and we note that other data sets from other sources might fare differently.…”
Section: Limitationssupporting
confidence: 83%
See 1 more Smart Citation
“…External validation will be important because our findings of patterns in vital signs measurements prior to neonatal death might reflect care practices at our hospital. We note, though, the similarity of vital signs measurements at our hospital to those at two others, 45 a finding that is reassuring with regard to the general nature of these results. We found that only 3555 of the 4998 algorithms consistently returned non-null results, and we note that other data sets from other sources might fare differently.…”
Section: Limitationssupporting
confidence: 83%
“…We did not analyze pre-term infants separately from term infants in this work, though we know that heart rate and SpO2 time series characteristics depend on both gestational age and postconceptual age. For example, the variabilities of heart rate and SpO2 rise with day of age, 45,46 and it is possible that highly-comparative time series analysis of pre-term infants might return different results from term infants. As it stands, there were many more term infants than preterm, but the latter represented more of the time series data.…”
Section: Limitationsmentioning
confidence: 99%
“…We found HR-SpO 2 cross-correlation to be the best individual feature to discriminate LOS vs. sepsis-ruled out events. 5 We also compared vital signs across our three collaborating sites and found clinically trivial though statistically significant differences in HR and SpO2 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to early recognition of disease states, sometimes hours before they would become clinically apparent [10]. ML algorithms can outperform HCPs in fulfilling this task, recognising the disease and supporting clinical decision making [7,[10][11][12].…”
Section: Ai Application In Real-time Routinely Recorded Neonatal Inte...mentioning
confidence: 99%
“…To evaluate how the model interacts with data throughout the infant's entire NICU stay, it should be subjected to continuous performance analysis, evaluating its output at every single timepoint [7]. Moreover, ML algorithms should be compared with current clinical tools in diagnostic accuracy, be subjected to internal validation and undergo generalisability testing with external validation [12].…”
Section: Ai Application In Real-time Routinely Recorded Neonatal Inte...mentioning
confidence: 99%